Angiotensin-1 Converting Enzyme I/D Gene Polymorphism: Its Prevalence and Association With Obesity Among Malaysian Malay Subjects - Yasrul Izad, Abu Bakar; Ahmad Zubaidi, A.latif; Nordin, Simbak; Atif, Amin Baig; Emilia, A (2017)
Angiotensin converting enzyme (ACE) has been identified as one of the candidate gene associated with obesity. ACE is central for the effective modulation of renin-angiotensin system (RAS). Ever since ACE gene has been reported to be polymorphic, numerous studies have been conducted to identify the distribution of I/D allele and its association with various diseases including obesity. This study sought to determine the genotypic and allelic distribution of ACE I/D gene polymorphism and its association with obesity in Malay subjects. This cross-sectional study including 217 Malay volunteers; 94 obese (BMI ≥30kg/m2 ) and 123 non-obese (18.5 ≤BMI ≤24.99 kg/m2 ) that were recruited following the inclusion and exclusion criteria of this study. Genomic DNA was extracted from the whole blood, and genotyping analysis was performed by means of allele-specific PCR. The ACE genotypic and allelic frequencies among the subjects were calculated and compared by Chi-Square test. Statistical significant was accepted at p < 0.05. Analysis of ACE I/D gene polymorphism in all subjects found frequencies of 51.6, 39.2 and 9.2% for the II, ID and DD genotypes, respectively. The allele frequency was 71.2% for the I allele and 28.8% for the D allele. Stratification of subjects according to obesity status showed no significant changes in the genotypic and allelic distribution of ACE gene in both groups, as the distribution of II, ID and DD genotypes in obese subjects was 47.9, 42.6 and 9.5%, respectively, while the I and D allele frequency was 69.1% and 30.9%, respectively. In nonobese subjects, the distribution of II was 54.5%, followed by ID (36.6%) and DD (8.9%). The allele frequency was 73.0% for the I allele and 27.0% for the D allele. The genotype and allelic distribution were similar in both groups and in accordance with Hardy-Weinberg equilibrium. This study demonstrates that the genotypic and allelic distribution of ACE gene was still lower than that reported in Western populations. Although it is not associated with obesity, further larger studies are required to validate our findings.